2006
DOI: 10.2174/156720106776359177
|View full text |Cite
|
Sign up to set email alerts
|

ADME Related Profiling in 96 and 384 Well Plate Format - A Novel and Robust HT-Assay for the Determination of Lipophilicity and Serum Albumin Binding

Abstract: The failure of about half of the drug candidates is associated with poor pharmacokinetic properties leading to a huge loss of time and money [1]. Early profiling of drug like properties provides important information in order to screen out insoluble, poorly absorbed and toxic compounds. Today, large compound libraries have to be screened, and of course the total number of compounds will rise over the next years leading to a growing demand for fully automated assays. A balance between quality, speed, throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The speed and simplicity offered by this approach has been somewhat superseded by the increased throughput of standardized in vitro methods utilizing whole plasma as detailed above. A variation on the HPLC methodology, TRANSIL technology, involves immobilization of HSA onto the inert surface of silica beads suspended in PBS buffer [46]. After compound addition and mixing, the beads are separated by low speed centrifugation and the resultant supernatant is analyzed by UV or MS. Validation has been performed on a range of compounds but there are few reported applications in the literature.…”
Section: Methodologies For Measuring Plasma Protein Bindingmentioning
confidence: 99%
“…The speed and simplicity offered by this approach has been somewhat superseded by the increased throughput of standardized in vitro methods utilizing whole plasma as detailed above. A variation on the HPLC methodology, TRANSIL technology, involves immobilization of HSA onto the inert surface of silica beads suspended in PBS buffer [46]. After compound addition and mixing, the beads are separated by low speed centrifugation and the resultant supernatant is analyzed by UV or MS. Validation has been performed on a range of compounds but there are few reported applications in the literature.…”
Section: Methodologies For Measuring Plasma Protein Bindingmentioning
confidence: 99%
“…It is a kinetic parameter related to lipophilicity, which in turn is related to the partition and distribution coefficients. Physicochemical profiling of drug molecules is important in assessing the potential for good oral absorption [11,12]. At the same time, physicochemical properties are not independent of each other, and effective use is in the collective assessment of these parameters.…”
Section: Passive Permeabilitymentioning
confidence: 99%
“…TRANSIL ® membranes are stable, unilamellar, ordered and fluid, as shown by DSC and NMR studies, enabling functional incorporation of the integral membrane proteins for receptor binding studies or screening tests [134]. Another advantage of TRANSIL ® based assays over the liposomal ones is the substantial density difference between the TRANSIL ® spheres and the assay medium, which enables a decrease the separation time from several hours for liposome-based tests to minutes for TRANSIL ® assays [135]. However, the method requires an independent concentration determination.…”
Section: Examples Of Particulate Systems For Hts Applications the Detmentioning
confidence: 99%
“…In addition, the system can be used in two "modes" including a high-throughput (HT) and a high-precision (HP) mode. In the latter, a broader range of lipid concentrations is used, improving the precision of the measurement [135]. It has been shown that the lipid composition of TRANSIL ® spheres can be easily modified which enables different barriers the drug must cross in vivo to be mimicked, for example, by introduction of negatively charged phosphatidylserine (PS) for drugs designed to pass through the blood-brain barrier which is rich in negatively charged compounds [136].…”
Section: Examples Of Particulate Systems For Hts Applications the Detmentioning
confidence: 99%
See 1 more Smart Citation